2018
DOI: 10.3389/fphys.2018.01440
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and Autonomic Regulation in Sleep Apnea Syndrome: A Potential Protective Role for Erythropoietin?

Abstract: Obstructive sleep apnea (OSA) is the most common form of sleep disordered breathing and is associated with wide array of cardiovascular morbidities. It has been proposed that during OSA, the respiratory control center (RCC) is affected by exaggerated afferent signals coming from peripheral/central chemoreceptors which leads to ventilatory instability and may perpetuate apnea generation. Treatments focused on decreasing hyperactivity of peripheral/central chemoreceptors may be useful to improving ventilatory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…There are emerging evidences for the neuroprotection effect of EPO both in vivo and in vitro [21,38,39]. The positive roles that EPO may play in APAC under higher dose, such as anti-apoptotic [12,13], anti-oxidant [14], and antiin ammatory [15,16] make it an ideal treatment in APAC. However, its role in angiogenesis, causing neovascularization is a dreaded occurrence in the eye [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are emerging evidences for the neuroprotection effect of EPO both in vivo and in vitro [21,38,39]. The positive roles that EPO may play in APAC under higher dose, such as anti-apoptotic [12,13], anti-oxidant [14], and antiin ammatory [15,16] make it an ideal treatment in APAC. However, its role in angiogenesis, causing neovascularization is a dreaded occurrence in the eye [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no research describing the changes of EPO and PDGF levels in APAC eyes. Recent studies have shown that both EPO and PDGF have neuroprotective functions such as anti-apoptotic [12,13], anti-oxidant [14] and anti-in ammatory properties [15,16]. Thus, the uctuations of their levels in aqueous humor may correlate with prognosis of trabeculectomy in APAC eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Its target receptors are expressed in several cell types including skeletal muscle [42][43][44][45][46][47][48][49]. EPO has a tissue protective potential, including anti-inflammation, anti-apoptosis, and improving metabolic alteration [48,[50][51][52][53]. EPO reduced cells apoptosis and inhibited pro-inflammatory cytokines in sepsis-induced lung injury model [54] as well as in kidney ischemia/ reperfusion injury model [55].…”
Section: Ivyspringmentioning
confidence: 99%
“…They are composed of type I glomus cells and type II glial cells. Type I cells respond to an impairment in blood flow and mainly to decreasing levels of arterial PO 2 (Andrade et al, 2018). The carotid body chemoreflex modulates sympathetic drive to the heart and vasculature to maintain blood pressure.…”
Section: Mechanisms Of Cih-induced Hypertensionmentioning
confidence: 99%